Implementasi Program Gotong Royong Cegah Stunting (Goceng) Di Kecamatan Cipondoh Kota Tangerang - Marcella Rahmawati; Nanan Sujana; Muhammad Ibrahim Rantau (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
Public policy is the concepts and principles that form the lines and basis of plans in carrying out work, leadership, and ways of acting (regarding orders, organizations, and so on). This policy can be implemented in government, the private sector and organizations. Policy is one of the things that is considered to be used in realizing a result from an action. The term implementation is usually associated with an activity carried out to achieve certain goals. One effort to realize this in a system is implementation. According to the law of the Republic of Indonesia Republic of Indonesia no. 25 of 2004 explains that a program is a way to implement policies that contain one or more activities carried out by the government/institution to achieve targets and objectives. Cpondoh District, Tangerang City created a program as a public policy for the community. However, there is still a problem with this program, namely that the community still does not want to participate and is still embarrassed if their children are categorized as approaching stunting, even though in Cipondoh District itself there are still children who experience stunting prevention. This research aims to determine the implementation of the Mutual Cooperation Program to Prevent Stunting (GOCENG) policy and determine the inhibiting factors and efforts made. This type of research is qualitative with a descriptive method that uses the results of analysis from Donald S. Van Meter and Carl E. Van Horn (1975) using 6 indicators, namely: Policy standards and targets 2. Resources 3. Characteristics of the implementing organization 4. Communication between related organizations and implementation activities 5. Disposition 6. Social, economic and political environment. The results of this analysis show that the Mutual Cooperation Program to Prevent Stunting (GOCENG) in Cipondoh District has not been successful because there are still obstacles.